THU0128 Do biological dmards prevent long term articular damage by rheumatoid arthritis in routine clinical care?. (12th June 2018) - Baghban, S.; Krens, L.; Henstra, M.; Vermeer, M.; van der Elst, K.; Bernelot Moens, H.
Abstract : Background: Treatment of rheumatoid arthritis is primarily aimed to achieve remission and thereby reduce the risk of permanent joint damage. Preventing disabling joint damage is an important long term goal for patients. Effectiveness of bDMARDs on disease activity has been proven in randomised controlled studies; however studies on long term joint damage are scarce and show conflicting results. 1, 2 Objectives: To compare joint damage more than 5 years after RA diagnosis in patients who have never used bDMARDs and in patients treated with bDMARDs. Joint damage is measured with the Rheumatoid Arthritis Articular Damage (RAAD) score, a clinical method comprising all joints that may be affected by RA. 3 Methods: Retrospective cohort study in RA patients in a Dutch teaching hospital diagnosed between 2006 and 2011. Inclusion criteria were receiving a DMARD for at least 12 months and availability of a RAAD-score after a disease duration of 5 years or more. Exclusion criteria was receiving a DMARD for an other indication than RA. The exposure of interest was the type of treatment (sDMARD or bDMARD). Results: Among 305 patients included, 101 used a bDMARD (table 1). Baseline characteristics were not significantly different in terms of prognostic factors for joint damage progression, with the exception of patients in the bDMARD group being younger. During follow up, the highest DAS28 was higher in the bDMARD group 5.0 vs 4.3, p<0.001. After 8.5 years, more than half of the patients in bDMARD (55.4%) and sDMARD (57.4%) groups had no joint damage (RAAD-score 0). No significant differences in long term joint damage were observed, even after adjusting for potential confounders (b=−0.26, 95% CI −1.9–1.4, p=0.76). Conclusions: In this cohort joint damage is not significantly different between patients treated with sDMARD(s) alone and those also using a bDMARD. Given the higher disease activity in the bDMARD group it is possible that this treatment prevented long-term joint damage by RA. Since there was limited joint damage in these groups this analysis should be repeated after longer disease duration and preferably in randomised cohorts. References: [1] Ciubotariu, et al. Joint damage progression in patients with rheumatoid arthritis in clinical remission. Do biologics perform better than synthetic antirheumatic drugs?J Rheumatol2014:1576–82. [2] Klarenbeek, et al. The impact of four dynamic, goal-steered treatment strategies on the 5-year outcomes of rheumatoid arthritis patients in the BeSt study. Ann Rheum Dis2011:1039–46. [3] Zijlstra, et al. The rheumatoid arthritis articular damage score: first steps in developing a clinical index of long term damage in RA. Ann Rheum Dis2002:20–3. Disclosure of Interest: None declared